Moondial - Cresswell, Helen (New York : Macmillan, 1987)
While staying with her mother's godmother, Minty finds herself drawn to a mysterious sundial which takes her back in time and links her life to that of two unhappy children she meets in two different centuries.
Kirkus Review.
School Library Journal.
7.0
7.0
5-8.
5-8
Keywords: Friendship -- Fiction; Time travel -- Fiction; Friendship -- Fiction; Space and time -- Fiction